Ali je vstavitev polževega vsadka varna metoda habilitacije in rehabilitacije gluhosti? - Gros, Anton (Zdravniški vestnik, 2011)
Background: The purpose of the study was to determine in which cases operativeand postoperative complications appear in deaf patients with cochlearimplants, the nature of these complications, and which of these complications require reoperations. Study subjects and methods: The study included 196 deaf persons (137 children and 59 adults), who had received cochlear implant for habilitation/ rehabilitation of their hearing ability in the period from March 1996 to the end of 2009 at the Department of Otorhinolaryngology and Cervicofacial Surgery in Ljubljana. The mean postoperative follow-up was 7 years (range 6 months to 13 years). Results: We did not register any serious operative or postoperative complications. In one case, the patient experienced significant intraoperative bleeding from emissary veins of the temporal bone, and in another case, significant leakage of perilymph from the cochlea appeared. In three cases, postoperative paralysis of the facial nerve was observed, which improved in the course of several weeks. Reoperation was required in 23 cases,. The most common reason for reoperation was a malfunction of the device (12 cases). This malfunction was more common in children. In two cases, we had to reoperate because of a misplaced electrode. In all cases we reimplanted the device in the same ear asin the first operation. In two cases, inflammation of the skin above the receiver appeared 6 and 14 months after the surgery. We excised the dead skin and covered the defect with a rotation skin flap. In one of the cases, inflammation of the skin flap reappeared, demanding removal of the device and new device implanted in the other ear. In two cases, purulent mastoiditis developed 8 and 11 months after the operation. (Abstract truncated at 2000 characters)
Keywords: kirurško zdravljenje; kohlearni implantant; zapleti